Sistem Manajemen Arsip Digital Berbasis Web - Annisa; Yahfizham (Journal of Research and Publication Innovation, 2024)
The web-based digital archive management system is a crucial solution to address the challenges of managing physical documents, which are often inefficient and prone to damage or loss. This research was chosen due to the importance of digitalization in facilitating easier access, storage, and maintenance of archives. The research methods used include user needs analysis, system design, and implementation and testing of the web-based application. This system is designed to allow users to upload, manage, and search digital documents easily and quickly. The research results indicate that this system significantly enhances the efficiency of archive management, reduces document search time, and ensures data security and integrity. With this system, users can access archives from anywhere and at any time, as long as they are connected to the internet. In conclusion, the implementation of a web-based digital archive management system not only improves operational efficiency but also provides a sustainable solution for archive management. This research is important as it demonstrates how technology can be utilized to enhance the efficiency and security of archive management, which is a critical aspect for many organizations.